The Effectiveness of the Implementation of Administrative Sanctions in Consumer Dispute Resolution in the E-Commerce Era under the Consumer Protection Law - Umar, Nurifana; Pujayanti, Luh Putu Vera Astri; Sabir, Muhammad; Kairuddin; Kasim, Aksah (Riau Law Journal, 2025)
The evolution of e-commerce due to digital transformation has introduced new issues in consumer protection, particularly concerning the efficacy of administrative penalties against digital enterprises. The primary issue in this study pertains to the ineffectiveness of administrative sanctions as stipulated in Law Number 8 of 1999 regarding Consumer Protection (UUPK), which remains anchored in the conventional transaction paradigm and has not adequately addressed cross-border and anonymous e-commerce practices. The objective of this research is to conduct a legal analysis of the efficacy of examine administrative punishments within the digital consumer protection framework, highlight normative and institutional obstacles to its execution, and propose alternative legislative changes for responsiveness. The methodology used is normative legal research using a regulatory and conceptual framework, supplemented by a study of secondary literature. The study's findings suggest the need to revise legislative regulations and enhance institutions by creating a digital oversight authority and developing a technology-driven integrated supervisory system. This change is crucial for guaranteeing legal stability and robust protection for consumers in the digital commerce age.